(untitled) (Social Security Management Journal, 2024)
This study investigated the impact of the knowledge and attitude of health care workers (HCWs) and their engagement in MSU prevention practice in Malaysia. One hundred and ten consenting HCWs participated in this cross-sectional survey. They responded to a structured questionnaire investigating socio-demographic and occupational characteristics, knowledge, and attitudes for the prevention of musculoskeletal conditions. The statistical data were analyzed using descriptive statistics and Pear-son’s chi-square test, which had a significant level of 0.05 using SPSS 27.0. The study utilized cluster disproportional simple random sampling. The study explored the relationship between healthcare providers’ knowledge and attitudes towards MSDs and their involvement in prevention practices. Results revealed a significant positive relationship between attitude and MSD prevention, while on the contrary, the relationship between knowledge and MSD was not significant. The study highlights the inadequate knowledge of MSD among HCWs and the need for improved availability of MSD knowledge, and special training on the utilization and interpretation of MSD. These implications underscore the importance of this research in improving the musculoskeletal health of healthcare workers, with the potential to impact healthcare practices and policies significantly.